Effect of a supramolecular delivery system based on hyaluronic acid with cyclodextrin on the antitumor properties of oxaliplatin in vitro - E. A. Pashkina; M. V. Bykova; M. T. Berishvili; Y. M. Zhang; V. A. Kozlov (Медицинская иммунология)
One of the modern approaches to the treatment of cancer is the creation of targeted delivery systems for anticancer drugs, which allows increasing the concentration of the delivered substance in the right place and preventing its accumulation in healthy organs and tissues. At the same time, one can also expect an increase in the duration and effectiveness of the drugs, as well as a reduction in side effects during therapy. The hyaluronic acid receptor CD44, which, according to the literature, is highly expressed in many types of tumors and regulates metastasis, is a promising target for targeted delivery of anticancer drugs. The purpose of this study was to evaluate the effect of a supramolecular delivery system based on hyaluronic acid with nanosized cavitand cyclodextrin on the antitumor properties of oxaliplatin in vitro. Cell lines 1301, SK-MEL-28 and B16 were used as tumor cells. Cells were cultured in the presence of a delivery system based on hyaluronic acid (HACD), oxaliplatin (OX), and their complex (HACD-OX) at various concentrations in complete culture medium RPMI-1640 containing 0.3% L-glutamine, 4% gentamicin and 10% inactivated FBS serum for 48 hours in a humidified atmosphere of 5% CO2 at 37°C. The effect of the studied compounds on the viability of cell cultures was assessed using the WST test. It was shown that in the case of the T-cell lymphoma cell line 1301, the HACD delivery system did not affect the ability of OX to reduce the viability of tumor cells of this line; the effect of free oxaliplatin and the complex was comparable. However, in the case of melanoma cells (B16 and SK-MEL-28), the HACD-DOX complex has a more pronounced antitumor effect, causing a statistically significant decrease in the viability of B16 and SK-MEL-28 cells compared to free oxaliplatin.